Development of High Strength-High Conductivity Cu-6 wt% Ag Alloy for High Field Magnet. Issue 17 (2016) - Sakai, Yoshikazu; Hibaru, Takaaki; Miura, Kiyoshi; Matsuo, Akira; Kawaguchi, Koushi; Kindo, Koichi
ABSTRACT: One of the authors developed the high strength and high conductivity Cu-24 wt% Ag alloy as a conductor material for high field magnets twenty years ago.Wire and sheet of the alloy have been used as a conductor material for pulsed magnets or resistive magnets of the high magnetic field facilities of each country. However, the alloy required large quantities of Ag addition to achieve high strength. The cost performance and workability of the alloy were not good for that. So, we investigated possibility of low Cu-Ag alloy for decreasing in material cost and improving in workability. We succeeded in the development of the Cu-6 wt% Ag alloy by the new heat treatment which is superior to the characteristic of the Cu-24 wt% Ag alloy even if the amount of Ag content is decreased in 1/4. At present, we make a lot of high field pulsed magnets by using the Cu-6 wt% Ag wire manufactured industrially, and do that magnetic field experiment and are getting good results at the ISSP, the university of Tokyo. We will talk about the characteristic, new heat treatment method and the manufacturing process of the conductor material for the Cu-6 wt% Ag alloy.